2011
DOI: 10.1002/jnm.763
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of radio‐frequency plasmas in N2

Abstract: SUMMARYThe structure of radio-frequency (rf) discharges in N 2 is examined for the electrons and positive ions, in which electron-neutral collisions and ion-neutral collisions are taken into consideration. Some detailed properties of rf plasmas sustained by an rf source voltage of 13.56 MHz and an amplitude of 200 V are presented using Monte Carlo simulation in electropositive gas (N 2 ). It is shown that most of the rf external electric field is absorbed in the sheath regions, whereas electrons respond easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…One basis of Monte Carlo simulation is random number generation [19]. The Monte Carlo simulation for radio frequency discharges was studied by Settaouti and Settaouti [20]. They found that the oscillations of the electron cloud determine the instantaneous sheath thickness near each electrode and most radio frequency external electric field is absorbed in the sheath regions.…”
Section: Numerical Solutionsmentioning
confidence: 99%
“…One basis of Monte Carlo simulation is random number generation [19]. The Monte Carlo simulation for radio frequency discharges was studied by Settaouti and Settaouti [20]. They found that the oscillations of the electron cloud determine the instantaneous sheath thickness near each electrode and most radio frequency external electric field is absorbed in the sheath regions.…”
Section: Numerical Solutionsmentioning
confidence: 99%